2014
DOI: 10.1371/journal.pone.0096115
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function of Endothelin-2 Leads to Reduced Ovulation and CL Formation

Abstract: Endothelin-2 (EDN2), a potent vasoconstrictive peptide, is transiently produced by periovulatory follicles at the time of ovulation when corpus luteum (CL) formation begins. EDN2 induces contraction of ovarian smooth muscles ex vivo via an endothelin receptor A-mediated pathway. In this study, we aimed to determine if EDN2 is required for normal ovulation and subsequent CL formation in?vivo. In the ovaries of a mouse model that globally lacks the Edn2 gene (Edn2 knockout mouse; Edn2KO), histology showed that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Prevention of EDN2 action in rodents using EDN receptor antagonists resulted in unruptured follicles that failed to develop into corpora lutea (CL; Ko et al 2006, Palanisamy et al 2006, Cacioppo et al 2014. Consistent with the contention that EDN2 is essential for CL formation, we reported that EDN2 mRNA levels were transiently expressed immediately after ovulation, in the early, developing bovine CL.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Prevention of EDN2 action in rodents using EDN receptor antagonists resulted in unruptured follicles that failed to develop into corpora lutea (CL; Ko et al 2006, Palanisamy et al 2006, Cacioppo et al 2014. Consistent with the contention that EDN2 is essential for CL formation, we reported that EDN2 mRNA levels were transiently expressed immediately after ovulation, in the early, developing bovine CL.…”
Section: Introductionsupporting
confidence: 65%
“…Endothelin 2 (EDN2) is a new player in reproductive processes implicated in ovulation and corpus luteum (CL) formation (Palanisamy et al 2006, Klipper et al 2010, Cacioppo et al 2014. Prevention of EDN2 action in rodents using EDN receptor antagonists resulted in unruptured follicles that failed to develop into corpora lutea (CL; Ko et al 2006, Palanisamy et al 2006, Cacioppo et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A similar expression pattern of ET2 was observed in CL of cows (Klipper et al 2010), implying a role of this peptide during luteal formation and angiogenesis. The physiological significance of ET2 in ovarian function was recently demonstrated in knockout mice, in which loss of ET2 expression resulted in impaired ovulation and luteal formation (Cacioppo et al 2014). Importantly, ET2 injection into ovaries of these animals augmented ovulation and increased expression of the cytochrome P450 side chain cleavage Luteal endothelin system in the dog enzyme (P450scc, CYP11A1) (Cacioppo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ET2 is the only ET that is upregulated in pre-ovulatory follicles at the time of ovulation and, as suggested for humans, rats and mice, its elevated levels might result from the hypoxic condition observed within growing follicles (Ko et al 2006, Na et al 2008, Bridges et al 2010, Choi et al 2011. The functional importance of ET2 and ETB for ovulation, CL formation and luteal P4 production was shown in mice (Palanisamy et al 2006, Cacioppo et al 2014. ETs also influence steroidogenesis through the activation of ETA (Iwai et al 1991, Tedeschi et al 1994, Kamada et al 1995, Girsh et al 1996.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation